MODEL BERMAIN PERAN DALAM MENINGKATKAN HASIL BELAJAR PADA KOMPETENSI DASAR MENERAPKAN PRINSIP-PRINSIP PELAYANAN PRIMA (Fakultas Ekonomi, Universitas Negeri Semarang, 2013)
The objective of the study was to improve the material mastery by using roleplay learning model which was indicated by at least 75% students got 75 for theirlearning achievement and all students were actively involved in the learning process. Itwas a classroom action research. The subject of the research was students at class XOffice Administration at SMK Negeri 2 Temanggung in the academic year of2013/2014. The study was consisted of two cycles which each cycle consisted ofplanning, implementation, action, and reflection. The data were collected by test andobservation sheets for students and teachers. The results of the study showed that: (1)Role play model can improve students’ learning achievement on the basic competenceof applying the principles of excellent service with the average of students’ learningachievement on the 1st cycle was 74.5, and rose up to 81.62 on the 2nd cycle, and theclassical completeness was 72.5% on the 1st cycle and increased up to 95% on the2nd cycle, (2) the students’ attitude toward learning was 63.10% on the 1st cycle andincreased up to 84.4% on the 2nd cycle.